Power mapping studies on the coil connection of an interior and embedded permanent magnet double stator generator - Ibrahim, Nur Amira; Misron, Norhisam; Hairulnizam, Hairul Faizi; Vaithilingam, Chockalingam Aravind; Mailah, Nashiren Farzilah; Aris, Ishak (Electromagnetic Academy, 2024)
The increased electrical demand in electrical machines promotes the improvement in power density in double stator systems. The power mapping performance and density of a novel type of interior embedded permanent magnet for a double-stator generator (IEDSG) is investigated in this work. This study investigates the basic attributes of the proposed IEDSG by analyzing various load resistances and changing rotor speeds. The Finite Element Method (FEM) is used to model the generation capabilities that consider electromagnetic properties such as flux density and flux lines. The proposed IEDSG is then manufactured and tested in a laboratory environment to assess how effectively it will perform when being paired with a load circuit. The efficiencies of two unique coil connections — series coil and independent coil — are evaluated and compared. According to the experimental results, when operating at an 800-rpm rotating speed, the independent-coil connection delivers a peak power output of 1688 W, a 16% improvement over the series-coil connection.